ARTICULACIÓN ENTRE COMERCIO INTERNACIONAL Y BIOTECNOLOGIA - Amador Berrocal, Sonia María (2005)
The commercial agreements subscribed at the international scope after the second half of the 1980’s, have increasingly emphasized the protection of new varieties of living beings obtained through genetic engineering. The widespread method used for securing property protection holds great parallelism with the patents system. This evidences an interest in protecting the products of the human mind, as a way of ensuring economic yields to the inventor, regardless of the nature or effects of the innovation. As a result of such interest, an approximation has occurred between two human activities, very distant from each other in the past, i.e.: Trade and genetic manipulation of living beings. The protection of copyrights is steered by several developed countries that invested large sums of money in biotechnological research decades ago and are now interested in recovering their investment with high yields. While indigenous people and peasants from poor countries offered their millenary knowledge gratuitously —preserved and transmitted for many generations— as well as the genetic biodiversity of their native environs, investors from rich countries charge exorbitant amounts for the biological material they return –with a high added value—in the form of patented seeds. Consequently, there is a clear absence of equity and an increasing subordination to more developed countries, both in the economic and scientific-technological areas.